The garden of love: some orthodox perspectives on the spirit and the Church - N. Dumitrascu (Acta Theologica)
In contemporary cultures, we often observe a strong shift of values. Traditional religious ones are being replaced with “worldly” – at times petty – values. Within this context, notion and understanding of “paradise” takes a central place. Indeed, this is frequently regarded as a consolation for failed ambition on earth, rather than as recognition of true communion with God. In fact, in paradise, human beings existed in a state of harmony with their Creator and the rest of creation, as well as with themselves. Due to the fall, human beings have been deprived of Grace. However, God sent the gift of His Son to recreate cosmic unity through His body, the Church. This article explores the manner in which the Church mysteriously shapes paradise life on earth.